Comparison of the Therapeutic Effects Between Isokinetic and Isotonic Strength Training in Patients After Total Knee Replacement: A Prospective, Randomized Controlled Trial. Issue 6 (21st June 2022) - Cheng, Yuan-Yang; Liu, Chuan-Ching; Lin, Shih-Yi; Lee, Cheng-Hung; Chang, Shin-Tsu; Wang, Shun-Ping
Background: Rebuilding the strength of the quadriceps as soon as possible after total knee replacement (TKR) is important so as to restore gait stability. To date, there are no standard postoperative strength training programs during the early recovery stage after TKR. Purpose: To compare the therapeutic effects between isokinetic and isotonic strengthening in patients after TKR. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: From April 2018 to August 2020, 37 patients met the inclusion criteria and were randomly assigned to perform either 4-week isokinetic or isotonic strength training programs. Other components of the rehabilitation program were kept the same between the 2 groups. All cases were evaluated by the Timed Up and Go (TUG) test, peak torque of knee extension and flexion (60 and 120 deg/s), 36-item Short Form Health Survey (SF-36), and Western Ontario and McMaster Universities Arthritis Index (WOMAC). Results: After undergoing a 4-week strength training regimen, significant improvements in the TUG test were noted in both groups; however, the time improvement in the isotonic group did not reach the minimal detectable change. All peak torque measurements improved in the isokinetic group but not in the isotonic group for knee flexion at 60 deg/s. The pain subdomain, physical domain, mental domain, total SF-36 score, and WOMAC index all improved significantly in both groups after training. Both training groups improved significantly in peak torque of knee strength, TUG test, and functional scores, but the differences between isokinetic and isotonic training were not statistically significant. Conclusion: The study findings showed that a 4-week strengthening exercise program in the early postoperative stage, involving either isokinetic or isotonic training, resulted in significant improvements in patients undergoing TKR. Registration: NCT02938416 (ClinicalTrials.gov identifier).